PRESENTATIONS OF AGLONA’S PILGRIM GROUPS: AUDIO-VISUAL CODES - Juško-Štekele, Angelika (Via Latgalica, 2017)
The article „Pilgrimage to Aglona: Audio-Visual Codes” is dedicated to Aglona pilgrimage, which is considered a significant element of intangible cultural heritage of Latvia. The importance of this tradition has been acknowledged by its vitality: in spite of the historical complexities, the tradition of Aglona ritual pilgrimage has survived for more than a century and in due course has strengthened its value in practice and social memory of the community. At the same time it is not a rigid value based in the past; instead it exists on its own and develops according to the dialectical patterns of ritual.The aim of the article is to investigate the most significant audio-visual codes featured in Aglona pilgrimage, by revealing the most distinctive expressions of identity among pilgrims and by highlighting the diachronic development of audio-visually perceptible attributes relevant to the pilgrimage. The subject of the research is a specific part of the pilgrimage ritual – presentations of pilgrim groups on Assumption Day of the Virgin Mary into Heaven on August 14, which are staged during the holy mass dedicated to pilgrims and youth. Typologically presentations staged by pilgrim groups are being viewed as a closure phase (postliminal rite) of a transition ritual (liminal rite).The article examines 93 presentations prepared by pilgrim groups in 2014, 2015 and 2016. For data acquisition an on-site observation was applied, which falls under the definition of the sensory anthropological meaning (Howes 2003:54). Analysis of presentations staged by pilgrims was conducted by means of structurally semiotic approach that allows defining the specific symbolic language of the pilgrimage while displaying sensory perceptible ritual codes of the pilgrimage – visual and audial codes, i.e. the visual attributes of pilgrim groups and verbally musical representations with their characteristic performative and reproduction elements.The visual code of pilgrimage refers to various aspects of social identity. The affiliation to religious identity has been presented by such religious symbols as cross, flags belonging to various congregations, religious movements or separate Christian communities, tablets with images of pilgrimage patrons and visualisations of the intent of participation in pilgrimage; locally patriotic identity has been attested by the flag of the country, region, municipality or city. The research confirms that religious symbols (especially cross) and the related ceremonies are becoming more modest, whereas locally patriotic representations are expanding, thus marking the geographical circumference of the pilgrimage and confirming Aglona as a sanctuary of international significance. The clothing of participants reflects either their professional identity (National Armed Forces, clergymen, nuns) or affiliation to a specific interest group (European Guides).The audial codes are explored within the repertoires of pilgrim presentations, appearing in the form of performance and reproduction. Metonymically, the audial codes in pilgrim presentations contain the most essential functions related to the ritual in general and demonstrate such inherent features of the postmodern culture as interplay of the traditional and the innovative. The traditional values have been represented by sacred symbols and topics, but the innovative by artistic performance techniques: method of exact dating, typological generalizations directed towards community identity generation, stylization of texts drawn from other cultural areas (folklore, pop culture). The verbal codes of pilgrim groups in turn manifest ambivalence that is inherent to the pilgrimage ritual in general and marks not only the text, but also a the dialogue among generations and values. The audio-visual codes being organically embedded in the symbolic system of pilgrimage ritual language reveal multi-layered dialogue on cultural values, which is present within the ritual at subject, text and action level.